2013
DOI: 10.1016/j.cellsig.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively active rhodopsin mutants causing night blindness are effectively phosphorylated by GRKs but differ in arrestin-1 binding

Abstract: The effects of activating mutations associated with night blindness on the stoichiometry of rhodopsin interactions with G protein-coupled receptor kinase 1 (GRK1) and arrestin-1 have not been reported. Here we show that the monomeric form of WT rhodopsin and its constitutively active mutants M257Y, G90D, and T94I, reconstituted into HDL particles are effectively phosphorylated by GRK1, as well as two more ubiquitously expressed subtypes, GRK2 and GRK5. All versions of arrestin-1 tested (WT, pre-activated, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 92 publications
(129 reference statements)
3
22
0
Order By: Relevance
“…This conclusion is supported by recent studies using rhodopsin-embedded nanodiscs, which have shown that one Rho* is sufficient for coupling to and activating G T (33)(34). Moreover, based on nanodisc reconstitution, monomeric rhodopsin has been shown to be sufficient for phosphorylation by G proteincoupled receptor kinase and interaction with arrestin (35)(36). The recent X-ray structure of a rhodopsin-arrestin complex (37) further illustrated that rhodopsin binds arrestin in a 1:1 stoichiometry.…”
Section: Structure-function Studies Of Rhodopsin-g Protein Signalingsupporting
confidence: 60%
“…This conclusion is supported by recent studies using rhodopsin-embedded nanodiscs, which have shown that one Rho* is sufficient for coupling to and activating G T (33)(34). Moreover, based on nanodisc reconstitution, monomeric rhodopsin has been shown to be sufficient for phosphorylation by G proteincoupled receptor kinase and interaction with arrestin (35)(36). The recent X-ray structure of a rhodopsin-arrestin complex (37) further illustrated that rhodopsin binds arrestin in a 1:1 stoichiometry.…”
Section: Structure-function Studies Of Rhodopsin-g Protein Signalingsupporting
confidence: 60%
“…4, Right Middle Inset), whose relative position has been implicated in arrestin-biased agonism in β-adrenergic receptors (36) and arrestin binding to rhodopsin (37). Also, the introduction of a salt-bridge between TM3 and TM7 by the night blindness causing rhodopsin mutant G90D reduces its ability to bind arrestin (38,39). Together, the finger and lariat loop could thus create an activity sensor that specifically interacts with helices critical for GPCR activation.…”
Section: Resultsmentioning
confidence: 99%
“…Principally such distinct conformations could control binding of arrestins either directly or more indirectly by favoring distinct phosphorylation patterns added by different GRKs. GRK1 and GRK2, for example, are able to promote high affinity binding of arrestin-1 to R*-P, whereas GRK5 was much less efficient [44 ]. Similarly, GRK2 and GRK3 effectively recruited arrestin-3 (also known as b-arrestin 2) for desensitization of vasopressin receptor V2, while GRK5 and GRK6 had much less influence on arrestin-3 recruitment [45].…”
Section: Phosphorylation-dependent Activation Of Arrestinmentioning
confidence: 97%